HUBUNGAN SELF CONFIDENCE DAN ANXIETY DENGAN PROKRASTINASI AKADEMIK PADA SISWA KELAS X MA DARUT TAQWA PURWOSARI PASURUAN - Aris Setiawan (Ilmu Psikologi Universitas Yudharta Pasuruan)
Procrastination is the behavior of delaying work or work with activities that are not important, so that the task becomes hampered and not completed on time. The results show that the hypothesis which states that there is a relationship between self confidence and anxiety with academic procrastination is accepted at a significance level of 1%, where Ry (1.2) = 0.71545039 is greater than Ftab 1% and F-count is 37.751 greater than Ftab 1% of 4.61. This shows that if self confidence and anxiety are high, academic procrastination is low, whereas if self confidence and anxiety are low then academic procrastination is high.